A taxonomic revision of the genus Xerodraba (Eudemeae, Brassicaceae) - Salariato, Diego Leonel; Zuloaga, Fernando O.; Al-Shehbaz, Ihsan A. (Phytotaxa, 2015)
Xerodraba is a South American genus distributed exclusively in the Andean-Patagonian region of southern Argentina and Chile. It is characterized by forming cushions with imbricate, scalelike leaves and solitary, terminal flowers. An updated taxonomic revision of the genus based on morphological analyses using both qualitative and quantitative characters is presented here. Xerodraba currently includes five species distributed in Argentina, of which two also grow in Chile. Xerodraba pectinata is reduced to synonymy of X. lycopodioydes, and X. pycnophylloides is treated as a subspecies of X. patagonica. The new combination X. patagonica subsp. pycnophylloides is proposed. Descriptions, keys to all taxa, updated geographical distributions, maps, and illustrations are provided.